Does microfinance alleviate poverty and inequality? Studying self-help groups in Bodoland, Assam. Issue 7 (3rd October 2017) - Maity, Shrabanti; Sarania, Rahul
ABSTRACT: This article aims to assess the impact of microfinance through a government-sponsored SHG–bank linkage programme (SBLP) of the National Bank for Agriculture and Rural Development (NABARD) in India, on poverty alleviation, employment, and achievement of financial inclusion in the Bodoland area of Assam. Empirical results from an impact evaluation showed that the programme had a positive and statistically significant impact on the monthly income, employment days, and financial inclusion level of participants of the SHG programme, compared to a control group of non-participants.